2015
DOI: 10.1016/j.anorl.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal lymphoma of the head and neck: A 67-case series

Abstract: ELHN is a rare pathology (5 cases per year in our department) of highly variable clinical presentation depending on location and histologic type. The ENT physician should be prepared for diagnosis regardless of anatomic location, so as to optimize diagnostic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 23 publications
8
38
0
2
Order By: Relevance
“…ENHL type of lymphoma affects patients with a median age of 68 years, with peak incidence in the 6th and 7th decades, although all ages may be concerned. Patients are more often male (Picarda et al, 2015).This is similar to the reported case. Lombard et al (2015) in the largest published series of 22 sinonasal lymphoma so far found that the presenting symptoms were poorly specific, with classic sinonasal functional signs: unilateral nasal obstruction, mucopurulent rhinorrhea, epistaxis and anosmia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…ENHL type of lymphoma affects patients with a median age of 68 years, with peak incidence in the 6th and 7th decades, although all ages may be concerned. Patients are more often male (Picarda et al, 2015).This is similar to the reported case. Lombard et al (2015) in the largest published series of 22 sinonasal lymphoma so far found that the presenting symptoms were poorly specific, with classic sinonasal functional signs: unilateral nasal obstruction, mucopurulent rhinorrhea, epistaxis and anosmia.…”
Section: Discussionsupporting
confidence: 79%
“…Lymphomas may originate from a lymph node or lymphatic tissue outside the lymph node (extranodal lymphomas). The extranodal lymphoma as mainly involve 4 sites: Waldeyer's ring, the nasal sinuses and fossae, the oral cavity and the salivary glands (Picarda et al, 2015). Lombard et al ( 2015) state that the main diagnostic problem is the lack of specific clinical signs, often leading to late consultation and thus diagnosis at an advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…28 While this multi-center Italian study does not provide additional insight into the incidence of ENKTL-NT in Europe, it is one of the few studies with only non-Hispanic whites. In contrast to the scarcity of ENKTL-NT reported throughout Europe, relatively large retrospective ENKTL-NT studies 26,27 and a prospective clinical trial have been completed in France. 29 This suggests that ENKTL-NT may be more infrequent, underreported, or misdiagnosed in certain parts of Europe compared to France.…”
Section: Estimating Global Incidence Rates Of Enktl-ntmentioning
confidence: 99%
“…RT'nin overlere etkisi yaşla azalır. Çocukluk çağında fertilitenin ve hormonal işlevle-rin sürdürülebilmesi için overlerin korunması çok önemlidir (1,4,11) .…”
Section: Hh Sağaltımında Cerrahinin Yeriunclassified
“…Laparoskopi bir kamera portu ve iki çalışma portu ile yapılabilmektedir. Keith iğnesi ile bilateral utero-ovaryan bağlar ve uterus posteriorundan dikiş geçilerek, her iki overin uterus süpero-posterioruna sabitlenmesi, ters Y pelvik radyasyon alacak hastalarda uygulanabilir (1,11,12) . Overlerin her iki köşesine birer metalik klips konması RT'de kılavuz görevi görecektir.…”
Section: Hh Sağaltımında Cerrahinin Yeriunclassified